2023
DOI: 10.3390/en16176198
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fossil Fuels, Renewable Energy, and Nuclear Energy on South Korea’s Environment Based on the STIRPAT Model: ARDL, FMOLS, and CCR Approaches

Grzegorz Zimon,
Dulal Chandra Pattak,
Liton Chandra Voumik
et al.

Abstract: This study intends to shed light on the environmental impacts of energy decisions in South Korea by analyzing the correlation between energy consumption patterns and environmental indicators such as carbon dioxide emissions. In 2021, global CO2 emissions increased by 6%—to the highest ever level of 36.3 billion tons—according to the International Energy Agency (IEA). This increase in CO2 emissions is a big problem for all countries around the world. The aim of this article is an analyze the impact of fossil fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…On the one hand, scholars have tried to figure out the relationship between urbanization and CEP. In general, unsustainable population growth would increase carbon emissions [26]; however, studies have indicated that there is no standardized relationship between urbanization and CEP, such as positive [27], negative [28], insignificant [29], inverted U-shaped [30], nonlinear [31], etc. On the other hand, researchers have focused on how urbanization affects CEP.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, scholars have tried to figure out the relationship between urbanization and CEP. In general, unsustainable population growth would increase carbon emissions [26]; however, studies have indicated that there is no standardized relationship between urbanization and CEP, such as positive [27], negative [28], insignificant [29], inverted U-shaped [30], nonlinear [31], etc. On the other hand, researchers have focused on how urbanization affects CEP.…”
Section: Introductionmentioning
confidence: 99%
“…Our research findings also suggest that the reversed “U"-shaped (EKC) curve is validated for these four countries. Moreover, the rise in squared GDP improves the environmental standards in South Asia [ 27 , 121 , 122 ]. According to our research analysis, renewable energy consumption is positively associated with carbon dioxide emissions.…”
Section: Discussionmentioning
confidence: 99%